2021
DOI: 10.4236/jmp.2021.128067
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Violation of Bell’s Inequality: A Misunderstanding Based on a Mathematical Error of Neglect

Abstract: This paper intends to show how the fabled violation of Bell's inequality by the probabilistic specifications of quantum mechanics derives from a mathematical error, an error of neglect. I have no objection to the probabilities specified by quantum theory, nor to the inequality itself as characterized in the formulation of Clauser, Horne, Shimony, and Holt. Designed to assess consequences of Einstein's principle of local realism, the inequality pertains to a li-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Hess found that it was also established in a random variables context by Vorobev [12]. Closely related results have been obtained in [13] [14], and possibly others, though they are little known to the community at large. While in the last line of (2.2) ( ) , C b b′ superficially appears to be the result of an independent measurement process and to have the same dependence on hidden variables as do the other correlations, its computation in fact reuses the data L. Sica from the previous correlations, data pair by data pair.…”
Section: The Constant In Bell's Inequality In Three Variablesmentioning
confidence: 69%
“…Hess found that it was also established in a random variables context by Vorobev [12]. Closely related results have been obtained in [13] [14], and possibly others, though they are little known to the community at large. While in the last line of (2.2) ( ) , C b b′ superficially appears to be the result of an independent measurement process and to have the same dependence on hidden variables as do the other correlations, its computation in fact reuses the data L. Sica from the previous correlations, data pair by data pair.…”
Section: The Constant In Bell's Inequality In Three Variablesmentioning
confidence: 69%
“…ations do not motivate a complete joint probability distribution for the polarization products constituting the linear combination that underlies Bell's inequality in a gedankenexperiment. The author of the present article has identified [2] precisely the four-dimensional convex hull of distributions that do cohere with the limited prescriptions of quantum theory in this regard. These do not specify a unique distribution for the gedanken quantity s which is defined as an unobservable combination of four polarization products on the same pair of photons.…”
mentioning
confidence: 86%
“…The substantive implications of quantum theory for the complete results of the experiment are imprecise. However, the author [2] has identified precise restrictions on distributions allowed by the theory that still respect local realism. These leave four free dimensions of agreeable probability vectors for the F. Lad imagined observation possibilities, and an identifiable convex hull of distributions within them.…”
mentioning
confidence: 99%
“…Hess found it previously discovered by Vorobov [8] [9] in the context of random variables. It has been extensively discussed by Lad [10] who pointed out that four such relations can be obtained from the inequality since each one can be generated from the other three. (Depending only on basic algebra, consequences following from this were given in [13]).…”
Section: Sicamentioning
confidence: 99%